Bioelectricity Generation Of Glycerine Waste In Microbial Fuel Cell - Zubir, Zulfahmi (Universiti Sains Malaysia, 2022)
Glycerin, commonly known as glycerol, is a byproduct of soap production and one of the biomasses. For every 100 pounds of soap made, 10 pounds of glycerine were generated, and the glycerine was often discarded. This creates an excess of waste over time and is harmful to the environment. By refining the waste glycerine into crude glycerol, some of the waste glycerine can be converted into a valuable product. The cost of refining is too expensive to be processed. A Microbial Fuel Cell may utilize the glycerine waste by converting it into energy. Utilizing the reduction and oxidation that occur as a result of the bacteria present in the glycerin, energy may be produced. In this study, a Dual Chamber This study aims to improve the power generation by using different parameter for the Microbial Fuel Cell and the material used on the cell. Some of the parameters are effect of concentration, effect of additive, effect of temperature and difference in electronegativity of the electrodes. The biofuel default concentration is set at 50% concentration. In this study , the electronegativity of material has the most influence in the maximum voltage yield where it improves the maximum voltage from 0.29V to 0.786V . The voltage generation improve by changing the electrode material where aluminium , copper and carbon are utilized and the maximum voltage yield are 0.596V , 0.354 and 0.29 repectively. The pH value of the solution in the anode and cathode chamber start to change by time when the MFC is operated by several days where at the anode the solution become more basic and at the cathode the solution starts to become acidic due to the presence of hydrogen ion in the solution Although the parameters have improved the voltage generation , but the power generation is still low and not suitable to be commercialized into the real world and more study needs to be done on the design of the MFC.